Strategi Pengendalian Alih Fungsi Lahan Pertanian di Subak Kerdung, Kelurahan Pedungan, Kecamatan Denpasar Selatan, Kota Denpasar - LATIEF IKHSAN; I WAYAN WINDIA; NI WAYAN SRI ASTITI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Strategy for Controlling the Transfer of Agricultural Land Functions inSubakKerdung, Sub-District of South Denpasar, Denpasar CityControl over the conversion of agricultural land is very necessary in order to maintainthe existence and sustainability of subak in the City of Denpasar, especially inSubakKerdung. There needs to be appropriate strategies as a solution so that controlover the conversion of agricultural land in SubakKerdung can be done. The purpose ofthis study was to determine internal and external factors and to find out the mostappropriate strategy in controlling the conversion of agricultural land in SubakKerdung.The results of the analysis of internal factors in SubakKerdung were: a) strength (theapplication of Tri Hita Karana in subak), b) weakness (low interest of subak members todefend their land). External factors were: a) opportunities (the development ofecotourism as a tourist attraction), b) threats (over the function of agriculturalland).Based on the SWOT analysis, the development strategies found were: (a) S-OStrategy - Optimizing the empowerment of farmer communities as the main actors inecotourism development by directly selling their agricultural products to tourists. (b) WOStrategy - Conducting education and training through counseling in adopting newinnovations so that agricultural products can be marketed to tourists. (c) S-T Strategy -Planting vegetables that have high economic value and can be processed into snacks anddrinks (d) The W-T Strategy -Implementing and increasing the intensity of educationand training on tour guides, i.e. English training for young people and farmingcommunities.